Impressions from the wild : a thematic analysis of adolescents' experience on Project K's Wilderness Adventure : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Wellington, New Zealand - Jones, Madeline Rose (Massey University, 2018)
Positive youth development (PYD) programmes empower adolescents by developing youth resources and strengths in order to meet their significant potential. Project K is a PYD programme developed and implemented by the Graeme Dingle Foundation in participating high schools around Aotearoa New Zealand. Year 10 students (age 14-15 years) are selected based on low self-efficacy scores relative to their year group. Low self-efficacy indicates that these students will benefit from the PYD opportunities Project K provides. The first of the three phases of Project K is the Wilderness Adventure, a 17-day wilderness experience which provides participants with first-hand mastery experiences in a novel and challenging outdoor environment. In groups of 12, adolescents take an active role in leading the group to complete kayaking, mountain biking, and hiking expeditions. This research explored the perspectives of 23 Project K participants on their Wilderness Adventure experience. Thematic analysis of eight focus group discussions identified two superordinate themes of challenges and outcomes, with three subordinate themes pertaining to each. The three challenge themes were outside comfort zone, real consequences, and interpersonal challenges. The outcome themes were mastery, attitude, and interpersonal skills. This study informs PYD programmes, particularly involving wilderness interventions, by communicating the experience of adolescent participants, and the challenges and outcomes that were perceived to be meaningful for them.
Keywords: Wilderness survival; Study and teaching; New Zealand; Outdoor recreation; Outdoor education; Youth development; Achievement motivation in youth; Youth; Psychology; Graeme Dingle Foundation